Cultural perceptions of illness in rural northeastern Thailand : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Nursing at Massey University - Nuntaboot, Khanitta; Khanitta Nuntaboot (Massey University, 1994)
In a transitional society like Northeastern Thailand, alternative and often competing therapeutic methods have been widely used by local people. Most illnesses are managed without recourse to the Government health care services. In Thailand there is a paucity of studies which explore and develop an understanding of how rural people regard illness in terms of causes and classification and how this knowledge influences what actions they take to deal with it. The impact of medical pluralism on illness management has rarely been studied in this country. The purpose of this study is to provide an understanding of the cultural meanings of illness for people in rural Northeast Thailand and their behaviour regarding health and illness care. An ethnographic approach, employing participant observation, interviews and ethnographic records, was selected as the research method, with fieldwork carried out in one rural village in Northeast Thailand where the researcher lived for 12 months. The findings suggest that what people do during an illness is guided by their healing knowledge which is experiential in nature. Mutual influences exist between people's beliefs about illness and their experiences of illness and healing methods. The experiential healing knowledge encompasses broad illness categories and beliefs in multiple causes of an illness. Multiple healing methods including both Western medicine and village curing methods are applied in any illness situation. Western medicine is believed to be effective to treat disease which is viewed as one part of illness, while village curing is believed to effectively treat other causes of illness as well as disease. Kin and neighbours actively participate in the articulation of illness situations, being involved in diagnosing the illness and identifying and prioritising multiple therapeutic management options. This description of people's perceptions of illness and its management, generated from the data, is crucial to increasing the knowledge base of members of nursing and other health professions. Such knowledge identifies critical aspects and possibilities for change in the practice of health professionals when working with rural people in Northeast Thailand. The study concludes with a discussion of strategies for practice and education which might be applied by nurses and other health professionals to improve the utilisation of available health care services.
Keywords: Thailand health care; Traditional medicine; Traditional health care; Health care services